Vegetation Community Structure of Mangroves in Sekilak Coastal Batam Riau Islands - Mukhti, Febrianto Roby; ', Efriyeldi; ', Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
A study of mangrove forests in Sekilak Coastal Batam Riau Islands was conducted in February 2014. The aim of this study was to determine the species composition, dominant species of mangrove and conditions in Batam Sekilak Beach. The survey method was used in this reaserch, where the observations were made with the belt transect method / belt transects. In the mangrove ecosystem was found 5 species of mangrove, included 3 families : Rhizophora apiculata, Rhizophora mucronata, Bruguiera gymnorrhiza, Xylocarpus granatum, and Lumnitzera littorea. Importance values was highest on the group tree Rhizophora mucronata 136,79% (Station 1), the highest importance values at station 2 was 103,37% and station 3 was 95,81%. In the group of seedling the highest INP was Rhizophora apiculata (163.68%) at Station 1, at station 2 on Rhizophora mucronata with INP 120,60%, and the highest INP at station 3, Rhizophora apiculata was 110,95%. Conditions of mangrove ecosystem at Station 1 can be categorized damaged by the criteria rarely. Station 2 and Station 3 in good condition with moderate criteria.Keywords: Mangrove, Sekilak Beach, Batam